2022
DOI: 10.1038/s41588-022-01245-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the genetic overlap between twelve psychiatric disorders

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 54 publications
7
34
0
Order By: Relevance
“…To our knowledge, the enrichment of SNP-annotations related to conserved genomic regions is the first of its kind for traits along the suicidality spectrum but was consistent across approaches. The magnitude of enrichment also was consistent with those reported for MDD [44] and across psychiatric disorders more broadly [47]. In the context of loci identified in GWAS of major depression, genes found in conserved regions of the genome were part of networks relevant for organismal development and function across the lifetime such as synaptic function and brain development [48,49].…”
Section: Discussionsupporting
confidence: 75%
“…To our knowledge, the enrichment of SNP-annotations related to conserved genomic regions is the first of its kind for traits along the suicidality spectrum but was consistent across approaches. The magnitude of enrichment also was consistent with those reported for MDD [44] and across psychiatric disorders more broadly [47]. In the context of loci identified in GWAS of major depression, genes found in conserved regions of the genome were part of networks relevant for organismal development and function across the lifetime such as synaptic function and brain development [48,49].…”
Section: Discussionsupporting
confidence: 75%
“…In this study we have investigated the role of rbfox1 in neurodevelopmental and psychiatric disorders by studying the behavioural effects of loss of rbfox1 function in zebrafish. This gene has previously been reported to be highly pleiotropic, contributing to several psychiatric disorders 13,14,28 . In addition, we have validated zebrafish rbfox1 sa15940 and rbfox1 del19 HOM lines as models of neurodevelopmental and psychiatric conditions.…”
Section: Discussionmentioning
confidence: 99%
“…RBFOX1 has not only been related to neurodevelopmental conditions, but increasing evidence points to both 3 rare and common variants in this gene as contributors to several psychiatric and neurological disorders 5,6,[10][11][12] . Interestingly, common variants in RBFOX1 were found significantly associated with the cross-trait phenotype of the most recent genome-wide association studies (GWAS) meta-analysis of psychiatric disorders 13 and RBFOX1 was identified as the second most pleiotropic locus in a previous cross-disorder GWAS meta-analysis, showing association of common variants with attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), bipolar disorder (BIP), major depression (MD), obsessive-compulsive disorder (OCD), schizophrenia (SCZ) and Tourette's syndrome (TS) 14 . Finally, Rbfox1 -/mutant mice present a heightened susceptibility to seizures and neuronal hyperexcitability 15 , and Rbfox1 neuron-specific knockout mice show pronounced hyperactivity, stereotyped behaviour, impairments in fear acquisition and extinction, reduced social interest and lack of aggression 6 , behaviours that are related to different psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…These results could arise from the sample sizes and power constraints of the available GWAS, as well as, from the higher heritability of certain disorders, including BIP and SCZ. However, very importantly, a recent article found out that MDD shows a very high polygenicity compared to other psychiatric disorders; that is, more genetic variants with weaker effects contribute to the overall genetic signal in MDD, and make the trait less annotatable 69 . In contrast, ADHD, BIP and SCZ showed the highest discoverability and hence a more annotatable genetic signal.…”
Section: Discussionmentioning
confidence: 99%